EVALUATION OF A NUMERIC METHOD FOR ALPACA FIBRE DIAMETER MEASUREMENT - González G., Haydeé (2008)
This study presents the statistical evaluation of a digital image alpaca fibre diameter measurement method, Digital Image Fibre Diameter Analysis (DIFDA). This method developed in the International Potato Center (CIP) requires an evaluation of the fibre sample digital image process, prepared in slides covers and taked from a scanner of negatives and films. DIFDA presents two options for fibre diameter measurement process: Digital image complete and sections of the digital image. The results of the fibre sample are mean fibre diameter, standard deviation and coefficient of variability. The objective was to test and compare the mean fibre diameter values obtained by DIFDA with the values from two conventionals methods: Projection Microscope and OFDA (Optical Fibre Diameter Analysis). In adition, DIFDA’s process options were evaluated. Two hundred six alpaca fibre samples from Pacomarca Farm, Puno, were evaluated. The mean fibre diameter samples values, measured by commercials methods, Projection Microscope and OFDA, were, 21.64 ± 3.58 and 21.74 ± 4.0, respectively. The mean fibre diameter reported for DIFDA was 21.74 ± 3.03. No statistical differences between the methods were detected. The Pearson’s correlation coefficient for DIFDA and Projection Microscope and for DIFDA and OFDA was 0.87 and 0.84, respectively. The process of DIFDA could be done in the complete digital image option, or using three or more sections for the dimention of 1000 x 1000 pixels, or five or more sections for the dimention of 500 x 500 pixels. The conclutions were that the DIFDA’s results showed no statistical significative differences between neither the Projection Microscope’s nor the OFDA’s results. Consequently, this measurement method would be used satisfactorily in breeding programs that requires continuos fibre measurement.